DIFFERENT-DEPTH XENOLITHS FROM DEVONIAN INTRUSIONS OF THE KOLA PENINSULA: KEY TO DECIPHERING PALEOGEODYNAMIC SETTINGS OF ALKALINE MAGMATISM - Baluev A.S.; Terekhov E.N. (My University, 2006)
One of the puzzles of intraplate alkaline magmatism is its spatial confinement to extensional structures (rifts), whereas manifestations of magmatism (massifs, diatremes, and dikes) are found in the areas characterized by horizontal compression. It is also difficult to explain the fact that magmatic rocks of this type are usually related to different mantle sources. In particular, coeval kimberlite and tholeiite diatremes are known within the Arkhangelsk province. The Kola province probably incorporates independent magmatic sources differently enriched or depleted in incompatible elements.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская